Forming new entrepreneur businesspeople: from the instrumental rationality of taylorism to a latin american substantive rationality - Ampuero Velásquez, Francisco Xavier; Echeverría Vásquez, Huber Gregorio; Salgado Arteaga, Francisco José; Ramos Ramos, Valentina (mktDESCUBRE; Vol 1 No 12 (2018): Twelfth Edition - (July - December), 2018)
The present review paper shows main aspects from Frederick Winslow Taylor´s work, most specially the ones related to the impact that his theory has had on teachers as well as on professionals linked to business management and entrepreneurship. His contribution to the evolution of the theories of organization will be reviewed in this article: on the one hand, the paper will discuss the intention to raise the administration of companies to a level of science, probably with methodological errors, and, on the other hand, it will analyze the dehumanizing effect generated by the use and abuse of entrepreneurs and managers who applied Taylorism and Fordism only as means and ends to achieve maximum profitability for companies. From the point of view of epistemology, a critique is presented regarding the functionalist and positivist method used to create scientific administration. The negative implications of the transfigured application of Taylorism are reiterated. This theory developed the instrumental rationality of companies over the substantive rationality of the subject, which has been questioned by several thinkers, from the Frankfurt School to the critical alternatives developed by the Latin American perspective. They should be known and taught to the next generation of entrepreneurs and managers, who have as their object of study the organization and its complexity.